Phosphorylation and disassembly of intermediate filaments in mitotic cells. - Chou, Y H (1989)
As baby hamster kidney (BHK-21) cells enter mitosis, networks of intermediate filaments (IFs) are transformed into cytoplasmic aggregates of protofilaments. Coincident with this morphological change, the phosphate content of vimentin increases from 0.3 mol of Pi per mol of protein in interphase to 1.9 mol of Pi per mol of protein in mitosis. A similar increase in phosphate content is observed with desmin, from 0.5 mol of Pi per mol of protein to 1.5 mol of Pi per mol of protein. Fractionation of mitotic cell lysates by hydroxylapatite column chromatography reveals the presence of two IF protein kinase activities, designated as IF protein kinase I and IF protein kinase II. Comparison of two-dimensional 32P-labeled phosphopeptide maps of vimentin and desmin phosphorylated in vivo in mitosis, and in vitro using partially purified kinase fractions, reveals extensive similarity in the two sets of phosphorylation sites. Phosphorylation of in vitro polymerized IFs by IF protein kinase II induces complete disassembly as determined by negative-stain electron microscopy. The results support the idea that the disassembly of IFs in mitosis is regulated by the phosphorylation of its subunit proteins.